A Controversial Role for IL-12 in Immune Response and Bone Resorption at Apical Periodontal Sites - Celso Martins Queiroz-Junior; Marcelo José Barbosa Silva; Jôice Dias Corrêa; Mila Fernandes Moreira Madeira; Thiago Pompermaier Garlet; Gustavo Pompermaier Garlet; Fernando Queiroz Cunha; Mauro Martins Teixeira; Tarcília Aparecida da Silva (Clinical and Developmental Immunology)
Periapical lesions are inflammatory conditions of tooth periapical tissues, triggered by dental pulp infection and characterized by exudation of immune cells to the affected tissues and production of inflammatory mediators such as cytokines. The inflammatory periapical reaction is mainly driven by Th1, Th2, and Th17 responses, and such polarization may modulate progression of the disease and expression of bone proresorptive cytokines. IL-12 is a potent inducer of IFN-γ production, which stimulates Th1 effector cells. Many evidences have shown a positive correlation between the bone resorptive cytokine IL-1β and the production of IL-12 and IFN-γ. Furthermore, IL-12 may have a potential role in the release of bone resorptive mediators and blockade of Th2 cytokines, affecting the progression of periapical bone loss. Nevertheless, IL-12 and IFN-γ have also been described as suppressors of osteoclast differentiation and activation, favoring bone maintenance. This paper focuses on the controversial roles of IL-12 in periapical lesions.